Proceedings of the 1st ACM SIGCHI/SIGART Conference on Human-Robot Interaction 2006
DOI: 10.1145/1121241.1121277
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of real world control of robotic assets under communication latency

Abstract: Robots are already being used in a variety of applications, including the military battlefield. As robotic technology continues to advance, those applications will increase, as will the demands on the associated network communication links. Two experiments investigated the effects of communication latency on the control of a robot across four Levels Of Automation (LOAs), (1) full teleoperation, (2) guarded teleoperation, (3) autonomous obstacle avoidance, and (4) full autonomy. Latency parameters studied inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(41 citation statements)
references
References 5 publications
1
40
0
Order By: Relevance
“…Operators needed to focus much of their visual attention on driving the robotic asset instead of using it for scanning and looking for targets. These findings are consistent with Luck, Allender, and Russell (2006) and Dixon et al (2003) that robotic operators demonstrated higher situational awareness when the robot's level of automation was higher. Luck et al suggested that the attention on (manual) robotic control might have distracted the operators from focusing on the vehicle's location, which was the study's measure of situational awareness.…”
Section: Discussionsupporting
confidence: 89%
“…Operators needed to focus much of their visual attention on driving the robotic asset instead of using it for scanning and looking for targets. These findings are consistent with Luck, Allender, and Russell (2006) and Dixon et al (2003) that robotic operators demonstrated higher situational awareness when the robot's level of automation was higher. Luck et al suggested that the attention on (manual) robotic control might have distracted the operators from focusing on the vehicle's location, which was the study's measure of situational awareness.…”
Section: Discussionsupporting
confidence: 89%
“…Auditory presentation of information can be combined with ongoing visual tasks (Helleberg et al 2003), and these improvements can be particularly important when dealing with multiple UVs, provided that they do not interfere with other auditory warnings (Donmez et al 2009). However, combining the control of a UV with other tasks can impair performance on target detection Wickens 2003, Chen 2008) and reduce situation awareness (Luck et al 2006). Draper et al (2003) compared speech and manual data entry when participants had to manually control a UV and found speech yielded less interference with the manual control task than manual data entry.…”
Section: Multimodal Interaction With Uvsmentioning
confidence: 99%
“…Chen et al suggested that maybe participants' teleoperation (i.e., driving the robot) negatively affected their target detection performance. Similarly, Luck, Allender, and Russell (2006) reported that situational awareness of UGV operators was better when the UGV had a higher level of automation. Luck et al suggested that the attention on (manual) robotics control might have distracted the operators from focusing on the vehicle's location, which was the study's measure of situational awareness.…”
mentioning
confidence: 92%